Artists of Cincinnati and vicinity - Cincinnati Art Museum. (The Museum, 1948)
Catalogue of an annual exhibition.
Exhibitions held at the Cincinnati Art Museum.
Vols. for 1952, 1957/58, 1958, 1959/60 and 1960/61 lack volume numbering.
Catalogue of an annual exhibition.
Keywords: Artists / Ohio / Cincinnati / Exhibitions / Periodicals.; Art, American / Exhibitions / Periodicals.